Peningkatan Kemampuan Pemecahan Masalah dan Berpikir Kritis Matematis Siswa melalui Pendekatan Metakognitif - Ainuna Fasha; Rahmah Johar; M. Ikhsan (Universitas Syiah Kuala, 2018)
Mathematical problem solving and critical thinking is two skills that need to be improved through learning mathematics. Metacognitive approach is one approach to improve them. This study aims to examine differences in the improvement of problem solving skills and mathematical critical thinking between students who get learning with a metacognitive approach and students who get conventional learning. This research is an experimental study with a pre-test post-test control group design research design. The population was all students of class XI of SMAN 3 Banda Aceh by taking samples of two classes, namely the experimental class and the control class through purposive sampling technique. Data collection was carried out using problem solving ability tests and mathematical critical thinking tests. Data analysis used t-test and analysis of variance. The results show that overall the improvement of students' mathematical problem solving and critical thinking skills that are learning with a metacognitive approach are better than students who obtain conventional learning, and there is an interaction between learning approaches and student ratings on mathematical problem-solving abilities